Application of a Novel CD206+ Macrophage-Specific Arterial Imaging Strategy in HIV-Infected Individuals. (16th February 2017) - Zanni, Markella V.; Toribio, Mabel; Wilks, Moses Q.; Lu, Michael T.; Burdo, Tricia H.; Walker, Joshua; Autissier, Patrick; Foldyna, Borek; Stone, Lauren; Martin, Amanda; Cope, Fred; Abbruzzese, Bonnie; et al.
Summary: In this proof-of-concept study, we present the first-in-human data suggesting that systemic administration of technetium Tc 99m tilmanocept ( 99m Tc-tilmanocept) enables noninvasive quantification of arterial CD206 + macrophages. Application of this macrophage-specific molecular imaging strategy highlights high-level aortic 99m Tc-tilmanocept uptake in human immunodeficiency virus and a relationship to noncalcified aortic plaque. Abstract: Background: The ability to noninvasively assess arterial CD206 + macrophages may lead to improved understanding of human immunodeficiency virus (HIV)–associated cardiovascular disease. Methods: We trialed a novel macrophage-specific arterial imaging technique. Results: We demonstrated colocalization between technetium Tc 99m tilmanocept ( 99m Tc-tilmanocept) and CD206 + macrophages ex vivo. In vivo application of 99m Tc-tilmanocept single-photon emission computed tomography/computed tomography revealed high-level 99m Tc-tilmanocept uptake across 20.4% of the aortic surface volume among HIV-infected subjects, compared with 4.3% among non–HIV-infected subjects ( P = .009). Among all subjects, aortic high-level 99m Tc-tilmanocept uptake was related to noncalcified aortic plaque volume (r = 0.87; P = .003) on computed tomographic angiography, and this relationship held when we controlled for HIV status. Conclusion: These first-in-human data introduce a novel macrophage-specific arterial imaging technique in HIV. Clinical Trials Registration: NCT02542371